Suratan kasih - V. N. Raj; Zulkeflie M. Osman ([S.l.] : SV Production)
Sebuah filem Melayu arahan Zulkeflie M. Osman
Copy available in DVD format
Penerbit eksekutif, Jeyakumar, Salehudin Ridzwan ; skrip, Anuar Idris ; penyunting, Mariam Ibrahim
Jamal Abdillah, Sofia Jane, Aida Aris, M. Rajoli, Khiril Anwar, Sidi Oraza
Keywords: Motion pictures -- Malaysia; Love in motion pictures; Malay drama